Changes in physical activity during hospital admission for chronic respiratory disease. Issue 7 (7th March 2019) - Orme, Mark W.; Harvey‐Dunstan, Theresa C.; Boral, Ismet; Chaplin, Emma J.L.; Hussain, S. Fayyaz; Morgan, Mike D.L.; Steiner, Michael C.; Singh, Sally J.; Greening, Neil J.
ABSTRACT: Background and objective: Establishing the amount of inpatient physical activity (PA) undertaken by individuals hospitalized for chronic respiratory disease is needed to inform interventions. This observational study investigated whether PA changes when a person is an inpatient, how long is required to obtain representative PA measures and whether PA varies within a day and between patients of differing lengths of stay. Methods: A total of 389 participants were recruited as early as possible into their hospitalization. Patients wore a PA monitor from recruitment until discharge. Step count was extracted for a range of wear time criteria. Single‐day intraclass correlation coefficients (ICC) were calculated, with an ICC ≥ 0.80 deemed acceptable. Results: PA data were available for 259 participants. No changes in daily step count were observed during the inpatient stay (586 (95% CI: 427–744) vs 652 (95% CI: 493–812) steps/day for day 2 and 7, respectively). ICC across all wear time criteria were > 0.80. The most stringent wear time criterion, retaining 80% of the sample, was ≥11 h on ≥1 day. More steps were taken during the morning and afternoon than overnight and evening. After controlling for the Medical Research Council (MRC) grade or oxygen use, there was no difference in step count between patients admitted for 2–3 days (short stay) and those admitted for 7–14 days (long stay). Conclusion: Patients move little during their hospitalization, and inpatient PA did not increase during their stay. A wear time criterion of 11 waking hours on any single day was representative of the entire admission whilst retaining an acceptable proportion of the initial sample size. Patients may need encouragement to move more during their hospital stay. Abstract : Objectively measured inpatient physical activity (PA) was examined for 259 individuals hospitalized due to an acute exacerbation of chronic respiratory disease. PA did not recover as an inpatient, with patients averaging 616 ± 649 steps/day. A single day of PA monitoring provided data representative of the entire inpatient stay. See related Editorial